PENGARUH FAKTOR SOSIAL EKONOMI TERHADAP KONTRIBUSI PENDAPATAN BURUH WANITA PEMBIBITAN KELAPA SAWIT DALAM PENDAPATAN KELUARGA DI PTP. MINANGA OGAN KABUPATEN OGAN KOMERING ULU - Lastinawati, Endang (Societa: Jurnal Ilmu-Ilmu Agribisnis, 2013)
ABSTRACT This study aims to calculate the income contribution and analyze the socio-economic factors that affect income contribution of women labor of oil palm seedlings. The study was conducted in Afdelling II Sei Ogan PTP. Minanga Ogan District of Ogan Komering Ulu. The location determination is done intentionally (purposive) by simple random sampling of 30 samples from 53 members of the population. The results showed that oil palm breeding female workers contributed income average of 35,35% of the average income family. Based on the regression results, socio-economic factors that significantly affect the revenue contribution of women workers in the oil palm nursery PTP. Minanga Ogan are age and income of the husband, while the level of education and number of family members is not  a real effect.